Figurative art in Bulgaria from the 1920s and 1930s: The School of Kyustendil, Kiril Tsonev and Boris Elisayeff - Dekova, Galina (Labyrinth, 2019)
The aim of this paper is to present those realistic tendencies in Bulgarian painting from the 1920s and 1930s, that echoe contemporary West European ones, like the New Objectivity in Germany. Among others, it will be shown how Bulgarian artist’s paintings are inspired by the folklore primitive from the past and reflect the assiduity of cultural administration to renew the idea of a modern artistic school of art with a defined national character.